Nurses’ Opinions on Ageism: A Phenomenological Study - Gamze YEĞİN; Songül KARADAĞ (Yaşlı Sorunları Araştırma Dergisi, 2025)
This study was designed to explore nurses' perspectives on ageism. A phenomenological design, which is one of the qualitative research methodologies, was employed. The sample of the study consisted of 8 nurses, and a focus group interview was conducted. No specific sampling criteria were applied; instead, nurses who agreed to participate and who were neither on leave nor on medical report during the study period were included in the research. With the participants’ consent, the interviews were audio-recorded and subsequently transcribed verbatim. Each session lasted approximately 60 minutes. A semistructured interview form was employed for data collection. The Nurse Information Form gathered demographic and professional data, including age, gender, marital status, educational background, income level, years of professional experience, current unit, work schedule, and duration of employment. The semistructured interview included seven open-ended questions. The data were analyzed using thematic analysis. All eight participating nurses were female, aged between 23 and 36, with professional experience ranging from 2 to 10 years. The findings were categorized under three main themes: “Perceptions of Aging,” “Views on Ageism,” and “Perceptions of Care for Elderly Patients.” Direct quotations were included to support the findings. The study concluded that nurses generally held positive perceptions toward elderly patients and that most did not exhibit age-based discriminatory attitudes. Providing inservice training is essential to enhance the quality of care delivered to elderly patients. Therefore, it is imperative for healthcare policymakers and authorities to implement well-structured planning and develop effective policies to address the existing economic and social challenges faced by the elderly population.